Analisis Framing Pemberitaan Penyalahgunaan Teknologi Kecerdasan Buatan Pada Foto Selebritas di Detik.com - Agustina, Sania; Despita , Dea; Sutaryat; Ramdani, Muhamad (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Advances in artificial intelligence (AI) technology have brought numerous conveniences to everyday life, particularly in the communications and digital content sectors. However, amidst these advantages, crucial issues have arisen regarding the misuse of these tools, particularly regarding the violation of personal privacy. One case of AI abuse that has captured public attention is the editing of images of famous figures to create imaginary images without their consent. This study focuses on how the media outlet Detik.com frames news related to the case of AI abuse in celebrity photos.The approach used is qualitative through framing analysis according to Robert Entman's model, encompassing four main aspects: problem identification, root cause analysis, ethical evaluation, and suggested solutions. Furthermore, the media advocates for strengthened regulations and increased public awareness to minimize the negative risks of technological advancements. Therefore, this study demonstrates the centrality of media framing in shaping public opinion regarding the moral challenges of implementing AI in virtual environments. The media also advocates for the establishment of legal regulations and increased public awareness to prevent the negative consequences of technological innovation. Therefore, this study strengthens the role of news framing in influencing public views on the ethical dilemmas of AI use in cyberspace